A PRELIMINARY STUDY OF CODE SWITCHING IN THE SPEECH OF AN INDONESIAN ENGLISH BILINGUAL - Grace Wiradisastra (Indonesian JELT, 2006)
This preliminary study of the speech of a bilingual shows that code switching is relatively spontaneous and follows the conventions of both languages. Code switching in this subject is generally triggered by an bilingual interlocutor whom the subject knows well. Many of the instances of code switching can be categorized according Gumperz’s discourse functions. However, it was found that the grammar of the code switches is not consistent and it cannot be predicted when code switching will occur. Keywords: bilingual, code-switching, bilingual interlocutor discourse function